Pelindungan Hak Ekonomi Terhadap Pencipta Sinematografi Digital: Studi Perbandingan Hukum Hak Cipta Indonesia dan Jerman - Praxedis Ajeng Pradita; Eddy Damian; Tasya Safiranita (Jurnal Hukum dan Sosial Politik, 2024)
Cinematographic work is protected by law under the Copyright Law No. 28 of 2014 in Indonesia. The fundamental principle is that the Creator is entitled to fair remuneration for the use of their work, in line with the alter-ego concept that gives the highest position to the Creator. In contrast to Indonesia, Germany has clearly regulated the procedures for the collection, management, and distribution of remuneration through the Urheberrechtsgesetz and the Collective Management Organization (CMO) operating with authorization from the Creator. The research method used is juridical-normative with a descriptive analysis approach. This study applies a comparative legal approach, utilizing data from both conventional and online literary sources, as well as interviews. The research findings indicate that Indonesia does not yet have specific regulations to protect the economic rights of digital cinematography. The absence of a Collective Management Organization (CMO) leads to an imbalance in licensing agreements between the Creator and digital platforms as users of cinematographic works.